The Master of Whitestorm - Wurts, Janny (New York : Grafton, 1994)
Only if two half-brothers, heirs to an ancient blood feud, work together can they lift the curse on the land of Athera.
"A Roc book."
Keywords: Fantasy fiction; Fantastic fiction